Effect of entrepreneurial networks on small firm performance in Kamrup, a district of Assam - Mandakini Das; Nivedita Goswami (Journal of Global Entrepreneurship Research, 2019)
The study is an attempt to examine the potential impact of entrepreneurial networks on small firm performance with the help of primary data. Dimensions of entrepreneurial networks used in this study are network structure (size, density and centrality) and network types (competitive and supportive). The population of the study consists of small firms of Kamrup a district of Assam. The analysis is done with the help of hierarchical regression model. The results reveal that network density and centrality have a positive impact on firm performance. However competitive and supportive network is not significant. The idea is to understand how small firm performances are important for policy makers, business advisors and other stakeholders to serve the business sector in a better way.
Keywords: 650; Entrepreneurial networks; Small firms; Performance; Assam